Analisis terhadap Pengelolaan Media Sosial KPP Pratama Padang Satu untuk Meningkatkan Literasi Perpajakan Masyarakat Melalui Instagram - Nova Sari Yudistia; Elva Ronaning Roem; Ernita Arif (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Society needs tax information that they could access in a faster and easier way without being restricted by space and time. Therefore, in the way to fulfill those society’s needs, KPP Pratama Padang Satu takes advantage of using the Instagram platform for publication media and communication media. This research intends to knowledge how the Instagram account of @pajakpadangsatu is being managed. The research method is qualitative with the ways of data collection utilized by interview, observation, and documentation study. This research applies the theory of social media management by Regina Luttrell which calls as The Circular Models of Some. This research then results in 6 (six) categories of content, those are activity content, taxation knowledge content, speech content, announcement content, performance achievement content, and entertainment content. The contents that are going to be shared with the public are packed in the best way dan followed the latest trend. The contents that are being uploaded usually involve a certain figure or public figure that already has performed tax obligations. This research found that several activities have not been done particularly at the optimization stage and the stage of managing media monitoring.